'Quarantine 15': Pre-registered findings on stress and concern about weight gain before/during COVID-19 in relation to caregivers' eating pathology. (1st November 2021) - Jordan, Amy K.; Barnhart, Wesley R.; Studer-Perez, Emma I.; Kalantzis, Maria A.; Hamilton, Lindsay; Musher-Eizenman, Dara R.
Abstract: The coronavirus disease (COVID-19) has dramatically altered daily activities including eating and physical activity behaviors, which in turn may be related to eating pathology. Those who care for children (henceforth caregivers) may face the brunt of these changes, but little research has examined the consequences of COVID-19 on eating pathology in caregivers. A community sample of caregivers ( N = 140) completed a cross-sectional online survey assessing demographics, stress and concern about weight gain before/during COVID-19, disordered eating (Eating Disorder Examination Questionnaire-Short Form), and emotional eating (Emotional Eating Scale-Revised). Significant positive relationships emerged between stress and concern about weight gain before/during COVID-19 and disordered eating, emotional eating-depression, emotional eating-anger/anxiety, and emotional eating-boredom. Stress and concern about weight gain during, but not before, COVID-19 positively predicted variance in disordered eating and emotional eating. Stress was associated with lower emotional eating-boredom when concern about weight gain during COVID-19 was low. Stress was associated with lower emotional eating-depression when concern about weight gain before COVID-19 was low, but when high, stress was associated with higher emotional eating-depression. Stress and concern about weight gain before/during COVID-19 may be relevant to worsened disordered eating and emotional eating in caregivers, a neglected population in the literature. Targeting concern about weight gain may weaken the relationship between stress and emotional eating-depression and emotional eating-boredom among caregivers in the context of the COVID-19 pandemic.